(untitled) (Research, Society and Development, 2021)
Introduction: In order to ensure the quality of food served in a Food and Nutrition Unit (UAN), several precautions need to be taken due to its complex functioning. It is necessary to evaluate and monitor the conditions of production and handling of these UAN’s. The great demand of the food service makes it a segment of great national relevance. In this context, it is of fundamental importance that the food units are submitted to evaluations of the production and handling of food, in order to guarantee the hygienic-sanitary quality, avoiding Foodborne Diseases (DOA). Objective: The aim of the study was to survey compliance rates in different food services in Brazil. Methodology: This is an integrative literature review (RIL) study, between the years 2010 to 2020, in which scientific articles that analyzed and classified the compliance of various food services in the Brazilian territory were selected. Conclusion: Therefore, in this study it was observed that, on average, the Food and Nutrition Units in different regions of Brazil have partially adequate hygienic-sanitary conditions. Non-conformities occur in all analyzed blocks, with a higher incidence in those that require documental registration. It is concluded that it is necessary that the sanitary control agencies focused on food have better control and strictness regarding the inspection of records, considering that the food offered in these environments must be of sanitary and nutritional quality.